1988
DOI: 10.1038/335639a0
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal cell killing by the envelope protein of HIV and its prevention by vasoactive intestinal peptide

Abstract: The clinical manifestations of AIDS (acquired immune deficiency syndrome) often include neuropsychiatric and neurological deficits, including early memory loss and progressive dementia. HIV (human immunodeficiency virus), the aetiological agent of AIDS, is probably carried by infected macrophages in the central nervous system. The virus enters cells by binding its envelope glycoprotein gp120 to the CD4 antigen present on brain and immune cells. From the data reported in this paper, we now suggest that the neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
245
4

Year Published

1989
1989
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 598 publications
(261 citation statements)
references
References 37 publications
12
245
4
Order By: Relevance
“…Recent reports on the neurotoxicity of gp 120 in cell culture suggested that signal transduction through an unknown surface molecule may disturb cellular tunetians by raising intracellular Ca 2 + concentrations ( Brenneman et al, 1988;Dreyer et al, 1990;Kaiser et al, 1990;Pulliam et al, 1991 ). When we measured intracellular Ca 2 + concentrations in D-54 cells in response to 0.01 to 1 J.Lg/ml rgp120, no increase of Ca 2 + Ieveis could be detected (Fig.…”
Section: Determination Of Intracellular Calcium Concentrationsmentioning
confidence: 73%
See 3 more Smart Citations
“…Recent reports on the neurotoxicity of gp 120 in cell culture suggested that signal transduction through an unknown surface molecule may disturb cellular tunetians by raising intracellular Ca 2 + concentrations ( Brenneman et al, 1988;Dreyer et al, 1990;Kaiser et al, 1990;Pulliam et al, 1991 ). When we measured intracellular Ca 2 + concentrations in D-54 cells in response to 0.01 to 1 J.Lg/ml rgp120, no increase of Ca 2 + Ieveis could be detected (Fig.…”
Section: Determination Of Intracellular Calcium Concentrationsmentioning
confidence: 73%
“…ln AIDS patients, this mechanism has been suggested to be responsible forT helper cell depletion (Ameisen and Caprone, 1 991) and could also cause cellular dysfunction and atrophy as observed in the brain (Fauci, 1988). ln addition, the HIV envelope glycoprotein gp 120 has been shown to increase intracellular Ca 2 + concentrations tagether with NMDA receptor agonists and to injure rodent neurons in vitro (Brenneman et al, 1988;Dreyer et al, 1990;Lipton et al, 1991 ). These mechanisms and the observed tyrosine phosphorylation in response to rgp120 in glial cells could provide a combination of signals leading to astrocytosis, impairment of myelin, and neurodegeneration as found in brains of AIDS patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,26 These effects can be modeled in mixed neuronal/glial cerebrocortical cultures from rodents or humans in which purified or recombinant gp120 initiates neuronal injury and apoptosis. 3,7,11,17,18,27,28 In order to further dissect the role of chemokine receptors in HIV/gp120-induced neurotoxicity, we used mixed neuronal/ glial cerebrocortical cultures prepared from wild-type (WT) mice or rats, and mutant mice deficient in CXCR4, 29 CCR5 30 or both chemokine receptors. Our findings suggest that, depending on the viral strain, HIV/gp120 can utilize CCR5 or CXCR4 or both receptors for induction of neurotoxicity.…”
mentioning
confidence: 99%